Quality Of Pie Skin From Corn Flour - andriyani, lusi; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
West Pasaman is the city with the highest corn production in West Sumatra. High corn production is mostly used for animal feed. The utilization of corn in West Pasaman in processed food is not optimal, even though corn has good nutritional content. Corn has the weakness of perishability, so it needs to be processed into semi-finished products such as flour so that it is resistant to storage and easy to apply to processed foods, such as pies. Pies vary a lot from the filling, so it is necessary to innovate the pie crust. The purpose of this study was to analyze the quality (shape, color, aroma, texture, and taste) of pie crust from corn flour as much as 20%, 30%, and 40%. This type of research is a pure experiment with a completely randomized design method (CRD) and uses primary data obtained from 5 expert panelists through a questionnaire. After the data was obtained, it was tabulated in the form of a table and an Analysis of Variance (ANOVA) was performed. If the analysis of variance shows Fcount Ftable, then it is continued with Duncan's test. The best results were found in X3 treatment with 40% corn flour substitution, therefore it is recommended for further researchers to use 40% corn flour substitution.